WAYS OF INCREASING THE EFFICIENCY OF INDUSTRIAL ENTERPRISES IN THE INNOVATIVE DEVELOPMENT OF THE SERVICE FIELD IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article examines ways to improve the efficiency of industrial enterprises in the innovative development of the service sector in the digital economy. The article also discusses the importance of constantly monitoring changes and adapting the strategy to new challenges and opportunities. The main factors that emphasize the need for this approach are discussed, such as a dynamic market, customer needs, the competitive environment, and technological advances. The authors emphasize that constant monitoring and adaptation of the strategy allows companies to be agile, innovative, and competitive, ensuring successful development in the long term.